Occupational Competence for Improving Industrial Enterprise Competitive Standards - Krčmarská, Lucie; Černý, Igor; Vaněk, Michal (GeoScience Engineering, 2013)
Success of enterprises is usually measured by their achievements. This success results from the competence of people working for the company. The employee competence can be understood as the sum of their actual performance and their latent abilities. Both is essential and provides for the competence completeness. Missing or inadequate occupational competences cause problems in running industrial enterprises, and thus a continuous improvement process of competence levels is a must. If a company is aware of the importance of people competences in relation to success or failures and strives to develop them, it is able not only solve current problems, but also remove causes of future problem incidences. This paper focuses on the assessment of the occupational competences and competence models as an important tool in the management of human resources.